150k views
3 votes
Can some one help please?!! I’m struggling

Can some one help please?!! I’m struggling-example-1

1 Answer

4 votes

Answer:

7x + 4y

Explanation:

We have to write an equivalent expression of the given expression in standard form.

The expression is - 5(x - 4y) + 2(6x - 8y)

= -5(x) - 5(- 4y) + 2(6x) + 2(- 8y)

{Applying the distributive property of multiplication}

= - 5x + 20y + 12x - 16y

= (-5x + 12x) + (20y - 16y)

{Separating the x and y terms}

= 7x + 4y (Answer)

User Mjswartz
by
5.5k points